NILAI-NILAI KEMANUSIAAN DAN PENDIDIKAN KARAKTER DALAM FILM GURU-GURU GOKIL KARYA RAHABI MANDRA - Fitri Cahyaningsih; Dessy Wardiah; Yenny Puspita (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to identify and analyze human values ​and character education.. This research is a qualitative research with descriptive method. This research was conducted in the film Guru-Guru Gokil by Rahabi Mandra. The data analysis technique used the intralingual equivalent technique. Data collection techniques using documentation techniques, observe and record. The results of the study show that there are behaviors that reflect human values, character education and sociology of literature in the film Guru Gokil by Rahabi Mandra. Human values ​​include: (1) the value of truth, (2) the value of peace, (3) the value of love or compassion, (4) the value of correct behavior, (5) the value of non-violence. The values ​​of character education include: (1) love of God and truth, (2) responsibility, discipline and independence, (3) trustworthiness, (4) respect and courtesy, (5) compassion, care and cooperation, ( 6) confident, creative, and never give up, (7) kind and humble, (8) tolerant and peace-loving.